2022
DOI: 10.1021/acs.inorgchem.2c01516
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evaluation of Metal–Ligand Bonding in Neptunium Compounds in Relation to 237Np Mössbauer Spectroscopy

Abstract: The 237 Np Mossbauer isomer shift and quadrupole splitting (QS) are powerful probes for the metal−ligand bonding of neptunium, a 5f-element of vital importance in the nuclear fuel cycle. A large set of Np compounds with different oxidation states (III) to (VII) is studied to investigate, by first-principles calculations, isomer shifts and the QS trends in relation to the Np oxidation state. Natural Bond Orbital analysis reveals that in addition to donation bonding to the 5f shell, participation of the 6d and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…For the orbital entanglement measurements, we found it necessary to use relatively large active spaces [e.g., MPS(24 e , 24 o )]. Previous MPS calculations of neptunium organometallic compounds demonstrated that small CASSCF spaces lead to overlocalization of the 5f shell and an underestimation of the ligand donation (dative bonding) 49 , 50 . Although (12 e , 12 o ) 51 and (8 e , 8 o ) 5 active spaces have been used previously to investigate the electronic structure of CUO, these active spaces appear to be insufficient to bring about a full picture of the bonding.…”
Section: Resultsmentioning
confidence: 99%
“…For the orbital entanglement measurements, we found it necessary to use relatively large active spaces [e.g., MPS(24 e , 24 o )]. Previous MPS calculations of neptunium organometallic compounds demonstrated that small CASSCF spaces lead to overlocalization of the 5f shell and an underestimation of the ligand donation (dative bonding) 49 , 50 . Although (12 e , 12 o ) 51 and (8 e , 8 o ) 5 active spaces have been used previously to investigate the electronic structure of CUO, these active spaces appear to be insufficient to bring about a full picture of the bonding.…”
Section: Resultsmentioning
confidence: 99%
“…11 To date, the EFG and NQCC values of a large number of nuclides have been theoretically studied in the literature, mainly focusing on Fe. 12–33 For systems containing heavy atoms, such as Bi, 6,34–39 U, 40,41 and Np, 42 relativistic effects become crucial and have been taken into account through various approximate or (nearly) exact methodologies. In the early 1970s, Desclaux and Bessis presented the first four-component Dirac calculation of EFGs.…”
Section: Introductionmentioning
confidence: 99%
“…58 Several comparisons have shown that the precision achieved by X2C in the EFG calculations is very close to that achieved in the four-component calculations. 36,55 Regarding the inclusion of electron correlation, most EFG calculations have been performed using density functional theory (DFT) methods, although several notable exceptions using advanced ab initio methods, such as coupled cluster methods [34][35][36][37][38][39][44][45][46]48,49 or multi-configurational methods 42 can also be found in the literature. It is noteworthy that DFT methods cannot accurately describe the electronic structure and properties of strongly correlated systems.…”
Section: Introductionmentioning
confidence: 99%